Hepatoprotective and Antioxidant Activity of Ethanol Extract of Cynoglossum zeylanicum (Vahl ex Hornem) Thurnb ex Lehm in CCl4 Treated Rats - Anitha M, Daffodil E.D., Muthukumarasamy S. and Mohan V.R. (Journal of Applied Pharmaceutical Science)
This study was designed to evaluate the hepatoprotective and antioxidant effect of ethanol extract of whole plant of Cynoglossum zeylanicum on CCl4 induced hepatotoxicity in rats. Activities of liver marker enzymes, SGOT, SGPT and ALP, total protein, albumin, globulin, total, conjugated and unconjugated bilirubins at an oral dose of ethanol extract of Cynoglossum zeylanicum (50, 100 and150mg/kg) showed a significant hepatoprotective effect. Regarding antioxidant activity, ethanol extract of Cynoglossum zeylanicum exhibited a significant effect showing increasing levels of SOD, CAT, GPx, GSH and GRD by reducing malondialdehyde (MDA) levels.
Keywords: Hepatoprotective activity,Antioxidant,CCl4,Bilirubin,MDA,GGT.